Radiofrequency-Induced Thermotherapy in Benign Prostatic Hyperplasia - Zargar Shoshtari, Mohammad Ali; Mirzazadeh, Majid; Banai, Masoud; Jamshidi, Meysam; Mehravaran, Kaveh (Urology Journal, 2009)
Introduction: We evaluated the efficacy and safety of radiofrequency-induced thermotherapy of the prostate in patients with benign prostatic hyperplasia (BPH). Materials and Methods: Radiofrequency-induced thermotherapy of the prostate was performed under local anesthesia in 24 patients (median age, 67 years) with BPH. The International Prostate Symptom Score (IPSS) score, maximum flow rate, postvoid residual urine volume, and prostate volume were measured preoperatively and 4 months postoperatively. Results: Nine patients (37.5%) had urinary retention preoperatively. One patient (4.2%) required transurethral resection of the prostate due to retention despite improved symptoms, and 2 (8.3%) needed an ?-blocker, postoperatively. The success rate was 87.5% after 4 months follow-up. All patients were catheter-free after the procedure. The mean IPSS score decreased from 26.08 ± 3.9 to 13.33 ± 4.69 (P < .001), and the mean maximum flow rate increased from 4.63 ± 4.4 mL/s to 13.21 ± 4.28 mL/s (P < .001). The mean prostate volume and mean residual urine volume were 46.38 ± 16.8 mL and 160 ± 57 mL, which decreased to 39.6 ± 16 mL (P = .009) and 61.46 ± 17.45 mL (P = .003), respectively. Fever, dysuria, and perineal pain (in 9 patients; 37.5%) were improved with conservative therapy. Retrograde ejaculation, erectile dysfunction, and urinary incontinence were not reported. Conclusion: Radiofrequency-induced thermotherapy of the prostate is a new, safe, and effective treatment for BPH. This technique is carried out under local anesthesia and mild sedation with little bleeding. It is especially appropriate for patients who present as high risk for general anesthesia.